Blockchain Technology for Modern Days and Future - Sapkota, Suman (My University, 2025)
Blockchain is a distributed ledger that is decentralized and used to store digital transactions and track digital assets. The blockchain term immutable ledger means that once any transaction is recorded, it cannot be manipulated or changed in any way. Blockchain's name comes from its structure, where a file consists of data blocks and each block is linked to the previous block, forming a chain. Each block contains transaction records or data records and contains a record of when that block was created or modified. Blockchain is designed to promote transparency, speed, reliability, efficiency and reliability in P2P and automated transactions. This topic examines the possibilities of using Blockchain technology in project management sit uations and in different sectors, creates a model mark and explains what the most important advantages of Blockchain technology and its future are. In addition, we will see the main con cepts and functions related to some of its main components, such as Bitcoin, smart contracts such as Ethereum, private distributed ledgers, etc. Blockchain technology is a new way to record transactions. It keeps these records, called blocks, in different databases, which we often call a digital ledger. We will see how Blockchain works, and one aspect of its use is in the form of tokens. The main idea behind this topic is that Blockchain technology has begun to conquer modern technology. So to explore how blockchain technology works today and what services Blockchain technology has, we will be understanding the different versions of Blockchain to get enough knowledge about how Blockchain works in the digital world. The study has created a block with the specified Hash function and executed it to create a blockchain. To deepen the understanding with Blockchain, this study shows how encryption tokens work in a Blockchain environment and will be creating a token sample that provides one of the most important uses of Blockchain tech nology today to represent tokenomics. This study also suggest the use of Blockchain usages in the project management sectors and its advantages that will revolutionize the future of working scenarios in different projects and clients.
Keywords: blockchains; distributed systems; virtual currency; cryptography; technology; payment systems; encryption; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Management; Strategic Project Management